Life Cycle of Municipal Wi-Fi - Chien-Kai Tseng; Kuang-Chiu Huang (International Telecommunications Society (ITS), 2017)
The popularity and growth of Internet usage and Internet enabled devices have changed the people life style and ways of communications. Mobile Internet usage increases year by year and have created prosperous Internet access market by myriad Internet service providers (ISPs). Mobile Internet operators and Wi-Fi service providers form complement and substitution relationships to offer Internet access options to enable anytime and anywhere services in many cities. From economics aspect, substitutes are often accompanied by market competition. In this scenario, municipal whether Wi-Fi would be treated as complement or substitute is an interesting question and incurs further consideration about what is the relationship between private ISPs and public ISPlife. Todeal with this question, we take three steps to analyze municipal Wi-Fi projects around the world to compare their development process and outcomes. To find a clear definition of municipal Wi-Fi is the initial step through gathering information from various municipal projects. Then, the study depicts the value chain of municipal Wi-Fi and adopts Porter's five forces analysis to discuss current municipal Wi-Fi development and illustrate its external competition picture. In five force analysis, municipality is treated as one of suppliers and local residents/tourists are users to analyze their bargain power of these Wi-Fi projects. Threats come from mobile Internet operators (MISPs) and other Wi-Fi service providers would challenge original goals of municipal projects. The interaction of bargain power and threats among these stakeholders affect the attitude and willingness about how do municipalities affect or manipulate their Wi-Fi projects. We adopt real option analysis (ROA) to discuss what kind of options that municipalities can select to evaluate Wi-Fi projects with flexibility as the last step. Through three steps study, we can offer a clear evolution picture of municipal Wi-Fi for its life cycle and address when are the transition points of municipal Wi-Fi projects. This paper extends previous studies about feasibility, goals and outcomes of municipal Wi-Fi projects to reveal the evolution path of municipal Wi-Fi projects and rethink whether these projects can be treated as public utility or just provisional services. Aside from its academia value, we expect this paper to be valuable to policy makers of municipal projects, Wi-Fi service providers and mobile Internet operators to assess value of Wi-Fi projects.
Keywords: 330; Municipal Wi-Fi project; Municipalities; Real options; Five-forces analysis; Development life cycle